The two different biliopancreatic limb lengths for roux-en-Y gastric bypass. (December 2019) - Mahmoudieh, Mohsen; Keleidari, Behrouz; Salimi, Mehdi; Sayadi, Masoud; Shahabi, Shahab; Sheikhbahaei, Erfan
Abstract: Background: Bariatric surgery is the most obvious way of treatment for morbid obesity and Roux-en-y Gastric Bypass (RYGB) is the most well-known technique. Meta-analysis results about the effects of Biliopancreatic limb length (BPLL) on weight loss and metabolic factors in blood remained controversial. This study aims to evaluate two different BPLL outcomes in obese patients. Methods: This retrospective cross-sectional study conducted on 64 obese patients who had RYGB indications in 2017. Small intestine bypassed length was 180 cm for all patients with a 40-mililitter gastric pouch. BPLL was chosen to be 130-cm in one group and 50-cm in another one. The Roux limb had the opposite length. Demographic data and metabolic factors assessed preoperatively and frequently evaluated in 1, 3, 6, and 12 months postoperatively. Results: Both methods were successful in promoting significant weight loss, however, 130-cm BPLL had significantly higher excess weight loss. Blood glucose index, lipid profile, albumin, and blood pressure were also reduced significantly in both groups during the follow-ups (P-value<0.001). Serum iron increased significantly in 130-cm BPLL group. Conclusion: Both short and long BPLL caused effective weight loss in non-super obese patients. Longer BPLL caused faster weight loss without any significant differences in metabolic factors. Highlights: Both limb lengths made significant decrease in BMI after 1 year. Both short and long BPLL caused effective weight loss in non-super obese patients. Longer BPLL caused faster weight loss without any significant differences in metabolic factors.